Reactions to Change in Romanian SMEs - Eduard Gabriel CEPTUREANU (Revista de Management Comparat International)
The scope of this paper is to explore how organizational change influences SMEs employees’ reactions to change. We identify some reactions based on individuals experience and explore conditions for developing such reactions. We rely on qualitative interview data from a study conducted in 2015 of reactions to planned change. We test employees’ reactions to change and show how they differ depending on their intensity of experience. The findings indicate that experience generate opportunities for employees to develop their change skills, which leads to more constructive responses to subsequent change initiatives. Yet, negative experiences can lead to mistrust behaviour that is based on cynical attitudes. The findings contribute by identifying experience based skills among subjects of change. Main limitation of the study is threat of self-selection as employees who remain in the organization may be more susceptible to mistrust behaviour. When employees have extensive change experience, entrepreneurs must adjust their way of thinking about change. Entrepreneurs need to be alert to the prominence of more mistrust behaviour. They should recognize their own role in generating positive process experience, which is a prerequisite for developing change skills at the employee level. The study adds to the increasing focus on change perspectives during change and shows how change skills can be developed among employees.